Resistensi Tradisional - Yansyah, Andri (INC- Islam Nusantara Center, 2024)
This article observes Haji Jole's contribution to the Bekasi community's resistance against the Allied Forces between 1945 - 1950. This figure's form of resistance was not a military model, using skills and weaponry like the regular army at that time, but rather a model of popular resistance, which relied more on makeshift weapons, in the form of everyday utensils. Nevertheless, Haji Jole had a mastery of martial arts to attack his opponents. This research uses the historical research method by using newspapers published in the relevant year as primary sources. This research found that there was a traditional resistance model launched by the figure of Haji Jole, which supported structural changes in Bekasi society to escape the influence of the Allies. Artikel ini mengobservasi kontribusi Haji Jole dalam perlawanan masyarakat Bekasi menghadapi Pasukan Sekutu antara 1945 – 1950. Bentuk perlawanan tokoh ini bukanlah model militer, yakni dengan menggunakan keterampilan dan persenjataan sebagaimana tentara reguler di masa itu, melainkan adalah model perlawanan rakyat, yang lebih banyak mengandalkan senjata seadanya, berupa perkakas sehari-hari. Kendati demikian, Haji Jole mempunyai penguasaan ilmu bela diri untuk menyerang lawannya. Penelitian ini menggunakan metode penelitian sejarah dengan menjadikan surat kabar terbitan tahun terkait sebagai sumber primernya. Penelitian ini menemukan adanya model resistensi tradisional yang dicanangkan lewan sosok Haji Jole yang mendukung perubahan struktural masyarakat Bekasi agar terlepas dari pengaruh Sekutu.